Acanthochephaliasis in White-lipped Green Pitviper (Trimeresurus insularis) - Panjaitan, Cahaya; Suprihati, Endang; Yudhana, Aditya; Hastutiek, Poedji; Wibawati, Prima Ayu (Jurnal Medik Veteriner, 2021)
White-lipped Green Pitviper (Trimeresurus insularis) is one type of snake whose population in nature is still not extinct and has a wide spread starting from the island of Java, Bali, Komodo, Lombok, Padar, Rinca, Romang, Roti, Sumba, Sumbawa, Timor. Population decline can occur if the incidence of disease infections continues to increase, one of the most common infectious diseases is helminthiasis. This study aimed to identify and determine the level of Acathochepala infection in White-lipped Green Pitviper in Banyuwangi Regency. A total of 20 green snakes were examined for Acanthochepala infection. Identification was done when the worm had been stained using carmine. The results showed that 20 positive green snake samples were infected with Acanthochepala in the subcutan, muscle tissue, digestive tract and reproductive tract.